Evaluation of a follow-up customized strategy for women treated with methotrexate for an ectopic pregnancy: An observational study. (May 2019) - Barbier, Magalie; Pivano, Audrey; Tourette, Claire; Poizac, Sabine; Cravello, Ludovic; Boubli, Leon; Agostini, Aubert
Abstract: Objective: To evaluate a follow-up customized strategy used in women treated with methotrexate for tubal ectopic pregnancy. Study design: This observational monocentric study took place from November 2009 to December 2015 in the emergency unit at La Conception University Hospital in Marseille, France. 440 women were treated by methotrexate for tubal ectopic pregnancy. Women were assigned in a classic follow up protocol with a weekly hCG evaluation (conventional protocol) if the drop in hCG between D1 and D4 was inferior to 20% or in an alternative follow up (streamlined protocol) with a hCG evaluation at one month. The main outcome measures were the success rate, the proportion of women requiring several methotrexate injections, and the mean number of consultations per women and duration of the follow-up. Results: During this period, the success rate was 348/440 (79.1%). The rate of women requiring 1, 2, or 3 injections and of women lost to follow-up were comparable between the two protocols. The mean number of consultations per woman was 3.6 ± 1.33 vs. 5.95 ± 2.25 days (p < 0.0001), and the follow-up was 27.5 ± 12 vs. 28.1 ± 15.4 (p = 0.6) respectively in the conventional protocol group and the streamlined. Conclusion: Our customized strategy allows for a decrease in the number of consultations per woman without changing the success rate or the need for methotrexate injection. hCG count drop between D1 and D4 allows for the selection of a low-risk group that can benefit from appropriate aftercare.